Powder diffraction study of some mixed ligand complexes of Mn(II), Ni(II), Cu(II), Zn(II), and Cd(II) - Ghose R.; Kumar R. (My University, 2025)
The mixed ligand complexes of manganese(II), nickel(II), copper(II), zinc(II), and cadmium(II) involving aspartic acid and benzoic acid have been synthesized. The complexes were studied by various spectroscopic techniques such as infrared, electronic, X-ray diffraction, and magnetic measurements. The complexes were found to have octahedral geometry. The X-ray powder diffraction results show that the crystal systems of Mn(II)-Asp-Ben complex are hexagonal, and Ni(II)-Asp-Ben, Cu(II)-Asp-Ben, Zn(II)-Asp-Ben, and Cd(II)-Asp-Ben complexes are found to be triclinic. The value of unit-cell parameters and XRD data for the five mixed ligand complexes are reported. © 2011 International Centre for Diffraction Data.